Antimicrobial Resistance Patterns and Plasmid Profiles of Methicillin Resistant Staphylococcus aureus Isolated from Clinical Samples - Agrahari, Gaurav; Koirala, Amrit; Thapa, Roshan; Chaudhary, Mahesh Kumar; Tuladhar, Reshma (Nepal Journal of Biotechnology, 2019)
Methicillin-resistant Staphylococcus aureus (MRSA), showing resistance to several antibiotics is a global health problem associated with considerable mortality and morbidity. Antibiotic susceptibility test is a commonly used method to characterize MRSA in epidemiologic studies. Additionally, plasmid profile has been reported to be useful in tracing the epidemiology of antibiotic resistance. This research was conducted to determine the antimicrobial resistance patterns and plasmid profiles of MRSA isolated from clinical samples at KIST Medical College, Imadol, Kathmandu, Nepal. All the clinical specimens sent to the laboratory were processed by standard microbiological techniques and antibiotic susceptibility testing was done by the modified Kirby Bauer disc diffusion method. Further, plasmid profiling was done by Alkaline-lysis method. A total of 27 (38.02%) MRSA were isolated from 71 S. aureus positive samples. MRSA showed the highest resistance towards penicillin (92.60%) and ampicillin (92.60%). In contrast, high levels of sensitivity were shown towards vancomycin (85.19%) and tetracycline (85.19%). Out of 27 MRSA positive samples, single plasmids were isolated from only 6 (22.22%) MRSA isolates. Antibiograms alone are inadequate to accomplish the characterization of MRSA during epidemiological studies. However, plasmid profile analysis in conjunction with the antibiotic susceptibility pattern is valuable in the epidemiological investigation of MRSA, and for reducing MRSA prevalence and treatment cost.